The first voyage round the world, by Magellan - Stanley, Henry Edward John Stanley, Baron, 1827-1903; Pigafetta, Antonio, approximately 1480-approximately 1534 (Works issued by the Hakluyt Society, 2010)
The text is translated 'from the Accounts of Pigafetta, and other Contemporary Writers. Accompanied by Original Documents, with Notes and an Introduction'. It includes the log-book of Francisco Alvo or Alvaro, Pigafetta's treatise on navigation and his account of the voyage, Gaspar Correa's account, other anonymous narratives, and documents relating to the cost and other aspects of the expedition. First published: 1874.